Risk Factor Acute Coronary Syndrome (ACS): A Systematic Review - Utami, Sukandriani; Biantara, I Made Putra; Arisarasmitha, I Gusti Ayu Kadek; Putri, Nurul Amiliana (Journal of Language and Health, 2025)
Acute Coronary Syndrome (ACS) remains the leading cause of morbidity and mortality globally, requiring a deeper understanding of its modifiable risk factors to inform prevention strategies. Objective: This study aims to identify the dominant risk factors contributing to ACS. Method: This systematic review synthesizes evidence from 11 peer-reviewed articles published between 2020 and 2025, sourced from PubMed and Google Scholar. Results: Among the studies evaluated, five major risk factors consistently emerged as significantly associated with ACS incidence: hypertension, smoking, diabetes mellitus, dyslipidemia, and obesity. Hypertension is the most commonly reported factor, demonstrating its important role in endothelial dysfunction and the development of atherosclerotic plaques. Smoking emerges as a strong and modifiable behavior-related risk, exacerbating oxidative stress and inflammation. Diabetes mellitus is associated with accelerated microvascular damage and atherogenesis, while dyslipidemia contributes through an imbalance of LDL and HDL cholesterol levels, promoting plaque formation. Obesity acts as an overarching metabolic disruptor, affecting four other risk factors through pathways involving insulin resistance and systemic inflammation. Conclusions: These findings reinforce the multifactorial etiology of ACS and highlight the urgent need for integrated public health interventions targeting these modifiable risks. Early identification and management of these conditions are critical to reducing the burden of ACS globally.